KEARIFAN LOKAL DALAM PEMANFAATAN DAN PELESTARIAN SUMBERDAYA PESISIR (Studi Kasus di Desa Panglima Raja Kecamatan Concong Kabupaten Indragiri Hilir Propinsi Riau) - Zulkarnain ' (Berkala Perikanan Terubuk, 2009)
The research was conducted in Panglima Raja Village ConcongSubdistrict Indragiri Hilir Regency of Riau Province. It was aimed to identify oflocal wisdom had been done in society of Panglima Raja Village. The researchwas done by case study or grounded research method.The result of research that there are local wisdom in exploiting andconserve coastal zone resources in Panglima Raja Village. Local wisdom thatidentified in exploiting of coastal zone resources in Panglima Raja are 1) decidedthe timing, weather, season in doing fishing 2) to develop traditional fishing gearin catch and collect the shell 3) decide the cutting zone the mangrove and thenlocal wisdom to conserve there are 1) the ceremony to honor the sea 2)commitment not to catch and kill the dolphin 3) believe there are secret zone 4)commitment not to throw the rubbish into the sea 5) commitment not to use ofsongko mesin in collecting the shell 6) guard the mangrove in coastal zone.